Prevalence of Site-Specific Mycoplasma genitalium Infection and Macrolide and Fluoroquinolone-Associated Mutations in Men Who Have Sex with Men in Shenzhen, China - Leng X; Zhu R; Ao X; Zhou Y; Zhang K; Hu T; Wu J; Chen Z; Huang L; Huang N; Li X; Ahmed Alnour R; et al. (Infection and Drug Resistance)
Xinying Leng,1,* Rui Zhu,2,* Xian Ao,1 Ying Zhou,3 Kechun Zhang,4 Tian Hu,4 Jiaxin Wu,1 Zhaoqi Chen,1 Lixia Huang,1 Nanxuan Huang,1 Xinyuan Li,1 Ruaa Ahmed Alnour,1 Zhantu Xue,1 Xiangcai Zhang,1 Han Liu,1 Tuerhongjiang Axirejiang,5 Wujian Ke,1,2 Huachun Zou6 1Dermatology Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2The First School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 3Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, People’s Republic of China; 4Longhua District Center for Disease Control and Prevention, Shenzhen, Guangdong, People’s Republic of China; 5The First People’s Hospital of Kashi Prefecture, Kashi, Xinjiang, People’s Republic of China; 6School of Public Health, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huachun Zou, School of Public Health, Fudan University, Shanghai, People’s Republic of China, Email zouhuachun@fudan.edu.cn Wujian Ke, The First School of Clinical Medicine, Southern Medical University, Email kewujianstauch@163.comBackground: Mycoplasma genitalium (MG) poses a growing public health concern due to the escalating antimicrobial resistance. We aimed to assess site-specific MG infection and its correlates and macrolide and fluoroquinolones mutations among men who have sex with men (MSM) in Shenzhen, China.Methods: Samples were obtained from different anatomic sites of MSM based on their sexual behavior. MG infection was detected using nested polymerase chain reaction (nested PCR). Identifying macrolide and fluoroquinolone resistance involved targeting the V region of the 23S rRNA, topoisomerase IV and DNA gyrase genes. Logistic regression was used to evaluate correlates of MG infection.Results: We collected 124 pharynx swabs, 132 urethral swabs, and 89 rectal swabs from 162 MSM participants based on their sexual behavior. MG was detected in 13.0% (21/162) of MSM. The prevalence of MG in the pharynx, urethra, and rectum was 9.7% (12/124), 6.1% (8/132), and 7.9% (7/89), respectively. Among the 21 MG-positive participants, 4.8% (1/21) were infected at all three sites, and 19.0% (4/21) were infected at two sites. Of the 27 MG-positive specimens, 22.2% (2/9) exhibited mutations at position A2071G, with A2071T being the predominant mutation in the 23S rRNA gene, accounting for 77.8% (7/9) of cases. Mutations in the parC and gyrA genes were detected in 33.3% (1/3) and 33.3% (2/6) of specimens, respectively.Conclusion: We observed a high prevalence of MG infections at different anatomic sites among the MSM population in Shenzhen, China. The high prevalence of macrolide and fluoroquinolone-resistant MG underscores the importance of implementing resistance-guided therapy, establishing surveillance networks, and exploring new antibiotics against MG.Keywords: antimicrobial resistance, Mycoplasma genitalium, MSM, macrolide, fluoroquinolone